TRAINING OF TRAINER PENINGKATAN KOMPETENSI PEMBELAJARAN ORANG DEWASA MELALUI MODULAR INSTRUCTION - Ari Bowo, Ahmad Nasir; Kusumawati, Intan; Putra, Aji Permana; Wahono, Joko (Gemi: Jurnal Penelitian dan Pengabdian, 2024)
The training of trainer service activities to increase the learning competence of adults or the elderly through modular instruction is motivated by a team of trainers who do not yet have experience as instructors or teachers, especially in the implementation of adult learning, including andragogy skills; (2) communication; (3) mastery of the material and class management. The training of trainers was held in the auditorium of Cokroaminoto University, Yogyakarta for one day. The purpose of the training of trainers is to improve the learning competence of adults or the elderly, before the trainers are deployed to the field, in this case the Sabilunnajah Islamic Boarding School, Sleman, Yogyakarta. The competencies in question are andragogic competencies or adult teaching skills, communication skills in implementing learning and classroom mastery and management abilities. The results of the training of trainers to increase the learning competence of adults or the elderly through modular instruction can be seen that: (1) the participants' andragogical skills on average are much better than before the training. Most of the participants had adult teaching skills which included indicators of understanding of older students, designing lesson plans, conducting learning evaluations, strategies for developing older students to actualize their various potentials. communication skills in the implementation of learning in general have been achieved more optimally including mastery or selection of sentences or words, ability to explain material, and voice intonation. (3) in general the mastery of the material is quite better, the participants are able to give instructions and the stages of delivering the material. The trainees understand the technical management of the class.